Kebijakan Politik Presiden Abdurahman Wahid: Upaya Penyelesaian Konflik Horizontal Di Maluku Utara - Saiful Ahmad (Jurnal Syntax Transformation, 2021)
The purpose of this study was to implement the political policy of President Abdurahman Wahid: Efforts to Resolve Horizontal Conflicts in North Maluku. The approach used is qualitative which is a case study, data collection techniques in the form of in-depth interviews, observations, documentation studies and Focus Group Discussion (FGD). This study took place in Ternate and surrounding areas, the study time in 2003-2004. The approach used is qualitative case study, data collection techniques in the form of in-depth interviews, observations, documentation studies and Focus Group Discussion (FGD). The results showed that the root cause of horizontal conflict in North Maluku is caused by two factors, namely, causal factors, and triggers. Among the causative factors are: repressiveness and resistance to the policies of the New Order government, low levels of education and the economy of society, weak social cohesion, religious sentiments, and weak government bureaucracy. While the trigger factor is; the ambition of local elite power, the seizure of territory and natural resources in Kao-Malifut, the existence of ethnic sentiments and collective competition, the influence of sara conflict in Ambon, refugees, and the circulation of Bloody Sosol documents.